Dominant environmental parameters for dust deposition and resuspension in desert climates. Issue 7 (3rd July 2018) - Figgis, Benjamin; Guo, Bing; Javed, Wasim; Ahzi, Said; Rémond, Yves
ABSTRACT: Field studies of dry deposition usually measure dust accumulation over periods of days or weeks. However, long measurement periods obscure the effects of meteorological conditions on the deposition rate. Previously we developed an "outdoor soiling microscope" (OSM) in order to measure dust deposition and detachment every 10 min in the field. In this study a greased/ungreased pair of OSMs was deployed for 51 days in the desert climate of Doha, Qatar. Stepwise regression analysis was performed to quantify the explanatory power of meteorological parameters on dust deposition and detachment rates. It was found that wind speed dominated deposition and rebound of dust particles, and produced a distinctive "threshold" response in deposition. The dry deposition results were highly consistent with a model by Kim et al. (2000) derived from outdoor experiments. By comparison, relative humidity and particulate matter concentration had less influence on dust flux rates. Copyright © 2018 American Association for Aerosol Research